2019
DOI: 10.1021/acs.jpcb.8b09704
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of a Multifunctional Amine and Phenol Surfactant with Ethanol on Hematite from Nonaqueous Solution

Abstract: Surfactants, which contain phenol and amine groups, are commonly used in industry to protect metallic surfaces and their efficiency depends strongly on factors such as pressure and temperature, solvent properties, and the presence of other surfactants in the system. In this work, we present a molecular simulation study of the competitive adsorption between a multi-functional phenol and amine surfactant model and ethanol at the oil/solid interface formed between iso-octane and a model hematite (α -Fe 2 O 3 ) sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Until recently, a certain surface coverage of surfactant molecules on the solid surfaces was usually assumed in MD simulations of OFMs. , However, Chia et al and Jaishankar et al used MD simulations to study the adsorption of surfactants on iron oxide surfaces from hydrocarbon solvents. Chia et al studied the competitive adsorption of the fuel additive 2-[(3-(dimethylamino)­propyl)­amino]­methyl-4-dodecyl-6-methylphenol and ethanol from isooctane onto the α-Fe 2 O 3 (0001) surface at different temperatures. They showed that while the free energy of adsorption of the additive was ∼2 times larger than that for a single ethanol molecule, a single additive needs to displace up to five ethanol molecules to strongly adsorb onto the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, a certain surface coverage of surfactant molecules on the solid surfaces was usually assumed in MD simulations of OFMs. , However, Chia et al and Jaishankar et al used MD simulations to study the adsorption of surfactants on iron oxide surfaces from hydrocarbon solvents. Chia et al studied the competitive adsorption of the fuel additive 2-[(3-(dimethylamino)­propyl)­amino]­methyl-4-dodecyl-6-methylphenol and ethanol from isooctane onto the α-Fe 2 O 3 (0001) surface at different temperatures. They showed that while the free energy of adsorption of the additive was ∼2 times larger than that for a single ethanol molecule, a single additive needs to displace up to five ethanol molecules to strongly adsorb onto the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Chia et al and Jaishankar et al extracted the potential of mean force (PMF) along the reaction coordinate using umbrella sampling (US) and the weighted histogram analysis method (WHAM). , Even with modern simulation software and high performance computing (HPC) architectures, this method is extremely computationally demanding and requires hundreds of nanoseconds of simulation time to obtain converged PMFs. For example, Jaishankar et al used an overall simulation time of more than 1 μs to obtain the PMF describing the adsorption of SA onto hematite from n -hexadecane.…”
Section: Introductionmentioning
confidence: 99%
“…27 Until recently, a certain surface coverage of surfactant molecules molecules on the solid surfaces was usually assumed in MD simulations of OFMs. 26,27 However, Chia et al 33 and Jaishankar et al 34 used MD simulations to study the adsorption of surfactants on iron oxide surfaces from hydrocarbon solvents. Chia et al 33 studied the competitive adsorption of the fuel additive 2-[(3-(dimethylamino)propyl)amino]methyl-4-dodecyl-6-methyl-phenol and ethanol from i-octane onto the α-Fe 2 O 3 (0001) surface at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 However, Chia et al 33 and Jaishankar et al 34 used MD simulations to study the adsorption of surfactants on iron oxide surfaces from hydrocarbon solvents. Chia et al 33 studied the competitive adsorption of the fuel additive 2-[(3-(dimethylamino)propyl)amino]methyl-4-dodecyl-6-methyl-phenol and ethanol from i-octane onto the α-Fe 2 O 3 (0001) surface at different temperatures. They showed that, while the free energy of adsorption of the additive was approximately two times larger than that for a single ethanol molecule, a single additive needs to displace up to five ethanol molecules to strongly adsorb onto the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation